Designing self-assessment questionnaire for Persian medicine in the field of education at Tehran University of Medical Sciences - Seyyed Hamid Kamali; Zahra Ghorbanifar; Shima Esfahani; Seyyed Ali Kamali (Babol University of Medical Sciences, 2018)
BACKGROUND AND OBJECTIVE: Evaluation of faculty members of the topics discussed that several methods including assessment by the authorities, and students, as well as self-assessment counterparts. Mastering technical skills self-evaluation as a powerful and dynamic tools and do it plays a key role in ensuring the quality of education and professional development. METHODS: The overall structure of the questionnaire, in line with the current rules package and upstream transformation and innovation of medical education, specialized knowledge, educational planning skills, teaching skills, management skills course and assessment of students ' skills and attention to community needs, health problems and providing training in traditional medicine. After collecting the opinions of stakeholders, analyze it and search again in the sources, and also confirm the validity of the formal content and inventory by the Assembly of experts, the staff of the Faculty the final version of the questionnaire was prepared. FINDINGS: This form can be used with the provision of feedback to make them aware of the way faculty members toward their strengths and weaknesses the activities, in order to improve, modify and improve the performance of the necessary training, planning and building new structures on the course to empower members of academic staff in cases of rated performance weaknesses based on the results of the evaluation design and implementation. CONCLUSION: It seems this form can be found on the side of the other evidence and documentation, with the conclusion of the evidence in order to the management decisions and incentive items used.